2021
DOI: 10.3390/app11094011
|View full text |Cite
|
Sign up to set email alerts
|

Research on Blockchain-Based E-Bidding System

Abstract: In the field of modern bidding, electronic bidding leads a new trend of development, convenience and efficiency and other significant advantages effectively promote the reform and innovation of China’s bidding field. Nowadays, most systems require a strong and trusted third party to guarantee the integrity and security of the system. However, with the development of blockchain technology and the rise of privacy protection, researchers has begun to emphasize the core concept of decentralization. This paper intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…These systems, in conjunction with smart contracts, pave the way for immutable and auditable decentralized auction systems [36]. A smart contract is a blockchain-based program (code) consisting of functions that are triggered by events and have predefined responses to these events.…”
Section: A Primer On Blockchainsmentioning
confidence: 99%
“…These systems, in conjunction with smart contracts, pave the way for immutable and auditable decentralized auction systems [36]. A smart contract is a blockchain-based program (code) consisting of functions that are triggered by events and have predefined responses to these events.…”
Section: A Primer On Blockchainsmentioning
confidence: 99%
“…In papers [6], [7], [8] and [9] explore the application of blockchain technology in different domains. Paper [6] focuses on a blockchain-based bidding mechanism for online auctions, highlighting its potential in improving transparency and security.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In papers [6], [7], [8] and [9] explore the application of blockchain technology in different domains. Paper [6] focuses on a blockchain-based bidding mechanism for online auctions, highlighting its potential in improving transparency and security. Paper [7] examines the synergy between blockchain and the Internet of Things (IoT), exploring how blockchain can enhance the trust and security of IoT systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that the sealed bid indicates constant and predictable behavior due to the simplicity of its architecture. Wang et al [18] proposed an e-auction system built on top of a permissioned blockchain (Hyperledger Fabric [19]). The use of a permissioned blockchain supported the system by reducing the probability of running into the risk of having distributed denial of service (DDoS).…”
Section: Background and Related Workmentioning
confidence: 99%